Estimation Depth For Stainless Steel Of Laser Spot Welding - Saktioto ' (Komunikasi Fisika Indonesia, 2012)
Penetration depth is one of the most important factors to the quality of a laser weld. In this investigation, two calculations are used to estimate the penetration depth for Stainless Steel 304L of laser spot welding. At laser power of 3500W, the calculations produce 0.0225m and 0.0226m penetration respectively. The power distribution into the material is given by the modified first order of Bessel function. The transmitted power will decrease according to the function, as the power penetrates the material. At the depth of 0.0226m and 0.0225, the power is given 3.9770W and 4.0981 respectively